METHODOLOGY OF USING DIGITAL TECHNOLOGIES IN INDEPENDENT TEACHING OUTSIDE THE CLASSROOM OF THE DEPARTMENT OF QUANTUM PHYSICS. - Mahmudov Furqat Jumaboyevich, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article highlights the benefits of using an electronic textbook and a virtual laboratory created in the LabIEW programming language. In particular, the use of a virtual laboratory created in the LabIEW programming language helps students develop motivation, better understand physical laws, analyze, observe and draw conclusions based on the results obtained. High efficiency highlighted.